Effect of Quantum Learning Model on Mathematics Learning Outcomes of Elementary School Students - Ahmad Rustam; I Made Rai Murdana; Ashri Usman (Universitas Sembilanbelas November Kolaka, 2022)
The background of this research is the low learning outcomes on the content of learning mathematics in fourth grade elementary school students. The purpose of this study was to determine the differences in learning outcomes of the quantum learning model and the conventional learning model. The research is a quasi-experimental design nonequivalent control group design. The population of this research is the fourth grade students of SD Negeri 2 Mowila and SD Negeri 5 Mowila as many as 83 students. The sample of this research is the fourth grade students of SD Negeri 2 Mowila (57 students) as the experimental group and the fourth grade students of SD Negeri 5 Mowila (26 students) as the control group. The research findings indicate that thelearning model quantum has an effect on students' mathematics learning outcomes. This is indicated by the results of the one sample t-test with sig. (2-tailed) of 0.00 (p 0.05). The effect of thelearning model quantum on mathematics learning outcomes with independent sample t-test test with value sig. (2-tailed) of 0.008 ˂ 0.05.